2021
DOI: 10.1109/tsp.2021.3089927
|View full text |Cite
|
Sign up to set email alerts
|

Deep Networks for Direction-of-Arrival Estimation in Low SNR

Abstract: In this work, we consider direction-of-arrival (DoA) estimation in the presence of extreme noise using Deep Learning (DL). In particular, we introduce a Convolutional Neural Network (CNN) that predicts angular directions using the sample covariance matrix estimate. The network is trained from multichannel data of the true array manifold matrix in the low signalto-noise-ratio (SNR) regime. By adopting an on-grid approach, we model the problem as a multi-label classification task and train the CNN to predict DoA… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(81 citation statements)
references
References 34 publications
0
42
0
Order By: Relevance
“…Recently, data-driven deep learning-based algorithms have been developed rapidly [31], and their strong nonlinear map-ping capability and robustness have attracted a lot of attention. In terms of DOA estimation, deep neural networks (DNN) [32], convolutional neural networks (CNN) [33], and convolutional recurrent neural networks (CRNN) [34], [35] yield very accurate estimation results through multi-label classification (MLC) or regression space spectrum. However, since the data-driven algorithms are very sensitive to data, while dynamic range of data is not taken into consideration, resulting in the network learning from the experience of prejudice to any fixed signal power during the training process [33].…”
Section: A Previous Work: Doa Estimation With Different Noise Typesmentioning
confidence: 99%
“…Recently, data-driven deep learning-based algorithms have been developed rapidly [31], and their strong nonlinear map-ping capability and robustness have attracted a lot of attention. In terms of DOA estimation, deep neural networks (DNN) [32], convolutional neural networks (CNN) [33], and convolutional recurrent neural networks (CRNN) [34], [35] yield very accurate estimation results through multi-label classification (MLC) or regression space spectrum. However, since the data-driven algorithms are very sensitive to data, while dynamic range of data is not taken into consideration, resulting in the network learning from the experience of prejudice to any fixed signal power during the training process [33].…”
Section: A Previous Work: Doa Estimation With Different Noise Typesmentioning
confidence: 99%
“…In the regime of internet of vehicles, [17] designed a fast beam alignment and tracking algorithm based on a hardware test platform to achieve vehicle tracking while performing millimeter wave communication with low latency and high data rate. As the research interest on ISAC keeps on increasing, more and more potential technologies are also introduced into this field, such as channel modeling [18], joint beam optimization [19] and machine learning [20], etc.…”
Section: B Related Workmentioning
confidence: 99%
“…We plug ( 18), ( 19) and ( 75) into (74), and absorb the constant term into the constant c, we obtain (20) Plugging ( 76) and ( 77) into (78), we obtain (75).…”
Section: Appendix Cmentioning
confidence: 99%
“…Chakrabarty and Habets [47], [48] demonstrate that a convolutional neural network (CNN) could be trained on white noise signals to estimate the DoA for a Uniform Linear Array (ULA). Other approaches also demonstrate the robustness of CNNs and fully connecter networks in low signal-to-noise ratio (SNR) scenarios [49], [50], [51], [52]. C ¸akır et al [53] showed that convolutive and recursive neural networks (CRNNs) could be used for sound event detection, followed by Adavanne et al [54], [55] who demonstrated CRNNs could estimate the DoAs for a specific class of sound.…”
Section: Introductionmentioning
confidence: 99%